Environmental economic valuation of the Interior Bay of Puno through choice experiments - Tudela-Mamani, Juan Walter (2023)
The ecosystem services provided by Lake Titicaca in the Interior Bay of Puno (BIP) are overused to stimulate local economic development without taking into account the environmental impacts produced. The objective of the research was to estimate the willingness to pay of foreign tourists visiting the BIP for the implementation of improvement alternatives on biodiversity, ecotourism boardwalk and decontamination of the bay. Semi-structured surveys were applied to national and foreign tourists (n=400) who visited the BIP during October 2019. Respondents chose their preferences regarding the implementation of ecosystem improvements and their willingness to pay for their implementation, through experiments. of choice and the use of mixed logit models. The attribute “biodiversity” is the most valued. The total WTP for the improvements in the three attributes is S/51.12/tourist, which would be included in the entry ticket to the BIP once the improvement proposals have been implemented. These results provide useful information for making appropriate decisions in interest groups and government authorities, focused on improving the management of ecosystem services in the BIP. The environmental management policies in the BIP must be focused primarily on the planting and management of reeds that allow better use, conservation and protection of the flora and fauna of the area.